Una mirada a París desde la alcantarilla: los “cuartos propios” de Alejandra Pizarnik - Ludmila Barbero (Cuadernos LIRICO)
In Alejandra Pizarnik’s work, spaces have a strong bodily presence, and, in turn, representations of the body are constructed with spatial references. We will dwell on certain spatial and spatio-corporal representations in the Diarios (2013) of the Parisian period (1960-1964) to see how the city and the “room of her own” appear there. Entries from previous years will be taken up for the analysis of space, and references to correspondence, particularly the Cartas Alejandra Pizarnik/ Leon Ostrov (2012). We will take upon the perspective that space and body are inseparable –as well as key elements– in Pizarnik's writing.